Influence of using different tapered longitudinal section manifolds in a Z shaped flat plate solar collector on flow distribution uniformity. (May 2022) - Karali, Mohamed A.; Alharthi, Mathkar A.; Refaey, H.A.
Abstract: This paper intentions to study the effect of using different tapered longitudinal section manifolds rather than the uniform one, in a Z shaped flat plate solar collector on; the uniformity of flow distribution, pressure drop, and consequently temperature profile. To this end, a 3D CFD model is planned to mimic a parallel piping network of Z configuration. Considering both fluid and piping body domains, and moreover, the inlet and outlet junctions, that would affect the resulted system pressure drop. The system has the following specifications: uniform header diameter of 20 mm, manifold and header lengths of 1150 mm, ten tubes, tubes diameter of 7 mm, tubes length of 1780 mm, horizontally mounted, and, with imposed solar radiation. Different taper ratios of the manifold, from 1.0 to 2.4 are studied against inlet ReD ranges from 300 to 2100. The model is validated with existing experimental outcomes from literature and showed an excellent agreement. Two indices are used to quantify the flow distribution uniformity. Generally the results concluded that, for enhanced flow distribution uniformity, an optimum taper ratio is important to be defined per each ReD .